Transcultural Appropriation on the Son Goku Character Configuration from Dragon Ball Manga - Abdurrahman, Dida Ibrahim (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018), 2018)
Configuration of characters in a story is a representative manifestation that is able to communicate the order and value of cultural distinctiveness inherent in him. Along with the phenomenon of globalization, through the practice of appropriation, the various exclusive elements and knowledge of certain groups of society are reconstructed into new cultural entities, even if they do not originate in the space and time in which they created. The configurations Son Goku in manga (typical Japanese comic) Dragon Ball is a transcultural myth of elements in the classic Chinese novel Journey to The West mixed with the popular modern serial story of Superman from the American DC Comics and King Kong, as well as the mythology of lycanthropy from Europe. Through further investigation, the source taken in the Son Goku configuration is suspected of having a relationship with elements and knowledge of different spaces and past times (archaic), so that he is not just a popular myth, he is a collection of texts from various cultural civilizations that are scattered all over the earth. Keywords: Transcultural Appropriation, Character Configuration, Son Goku.